Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/ctm2.1103
|View full text |Cite
|
Sign up to set email alerts
|

Elevated ubiquitination contributes to protective immunity against severe SARS‐CoV‐2 infection

Abstract: Background The crosstalk between the ubiquitin‐proteasome and the immune system plays an important role in the health and pathogenesis of viral infection. However, there have been few studies of ubiquitin activation in severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection. Methods We investigated the effect of ubiquitination on SARS‐CoV‐2 infection and patient prognosis by integrating published coronavirus disease 2019 (COVID‐19) multi‐transcriptome data and bioinformatics methods. Results The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…The ubiquitination level in COVID-19 patients has been proposed as a potential prognostic indicator, as well as a promising target for therapeutic intervention [105]. In this study, Che et al (2022) utilized COVID-19 transcriptome data and bioinformatics to explore ubiquitination in COVID-19 patients.…”
Section: Erad/ups-related Antiviral Strategies Against Sars-cov-2mentioning
confidence: 99%
“…The ubiquitination level in COVID-19 patients has been proposed as a potential prognostic indicator, as well as a promising target for therapeutic intervention [105]. In this study, Che et al (2022) utilized COVID-19 transcriptome data and bioinformatics to explore ubiquitination in COVID-19 patients.…”
Section: Erad/ups-related Antiviral Strategies Against Sars-cov-2mentioning
confidence: 99%
“…In addition, they proved that I3C is able to block SARS-CoV-2 viral egression in the Vero E6 model through the inhibition of HECT proteins implicated in COVID-19 pathology. The importance of E3 ligases in the ubiquitination of some viral proteins has recently been confirmed by combined multi-omics studies that have allowed the demonstration of the ability of SARS-CoV-2 not only in the remodeling of innate immunity, but also in promoting viral infection, by hijacking specific processes of ubiquitination [ 138 ]. The role of ubiquitination processes in the survival of the virus have also been very recently confirmed by a study that demonstrated how ubiquitin variants are able to inhibit the production of new viral particles after infection, thus preventing the virus from spreading from one cell to another and wreaking havoc in the body [ 139 ].…”
Section: I3c Natural and Exogenous Synthesis In Vitro And In Vivo Act...mentioning
confidence: 99%